The Relationship of Nutritional Status on Female Santri's Menstrual Cycle in Al-Jihad Islamic Boarding School in Surabaya - Rusdi, Warda Elmaida; Farindra, Irmawan; Rusdi, Muhammad Salsabeela; Farmananda, Irsandi Rizki; Benge, Wilhemus D.M.R (Jurnal Medis Islam Internasional, 2024)
Introduction: Menstruation is triggered by the monthly period, which creates the menstrual cycle. Several factors can lead to irregular menstrual cycles, including stress, smoking, taking hormonal supplements, disorders of the endocrine system, and nutritional deficiencies. Objective: This research aims to investigate the connection between nutritional status and the period of menstruation in female students at Al-Jihad boarding school in Surabaya, Indonesia. Methods: This study was conducted using an analytic observation approach. The research sample was determined using a simple random sampling technique, according to the inclusion and exclusion criteria that had been set. Questionnaires were used as data collection instruments, and anthropometric examinations were conducted to assess nutritional status and the menstrual cycle. Univariate analysis and bivariate analysis were performed to analyze the data. The chi-square statistical test was used as a bivariate analysis with a p-value <0.05 indicating significant data. Results: A total of 65 respondents were used in the study because they met the inclusion criteria. Based on the survey results using questionnaires and anthropometric examinations, it was found that 4.6% of female students had an obese nutritional status, 7.7% were obese, and the remaining 87.7% were normal. The menstrual cycle experienced by female students is 27.7% of female students experience an abnormal menstrual cycle, and the other 72.3% have a normal menstrual cycle. Based on the Chi-Square test, the significance value of p = 0.290 means no relationship between nutritional status and the menstrual cycle. Conclusion: The menstrual cycle in adolescence is not influenced by nutritional status.